Risk factors for non compliance using occlusive therapy: a case study - Lança, Carla Costa (2011)
Purpose: compliance with treatment is a common problem when treating amblyopic patients. Visual acuity of amblyopic eye does not improve without effective occlusive therapy. The aim of this study is to identify potential risk factors of non-compliance with treatment when it is implemented by family in amblyopic children. Setting: a quantitative transversal study was performed in a public hospital and in a private clinic in Lisbon.